Maillard Reaction Induced Changes in Allergenicity of Food - Jingkun Gou; Rui Liang; Houjin Huang; Xiaojuan Ma (Foods, 2022)
Food allergy is increasing in prevalence, posing aheavier social and financial burden. At present, there is still no widely accepted treatment for it. Methods to reduce or eliminate the allergenicity of trigger foods are urgently needed. Technological processing contributes to producing some hypoallergenic foods. Among the processing methods, the Maillard reaction (MR) is popular because neither special chemical materials nor sophisticated equipment is needed. MR may affect the allergenicity of proteins by disrupting the conformational epitope, disclosing the hidden epitope, masking the linear epitope, and/or forming a new epitope. Changes in the allergenicity of foods after processing are affected by various factors, such as the characteristics of the allergen, the processing parameters, and the processing matrix, and they are therefore variable and difficult to predict. This paper reviews the effects of MR on the allergenicity of each allergen group from common allergenic foods.